Short-term effects of ophthalmic topical 0.01% atropine on the ocular surface, pupil size, and subsequent subjective quality of vision in young myopic Chinese adults - Li, Mingze; Chen, Yimeng; Chen, Jiayan; Qin, Guanghao; Li, Liangzhe; He, Wei; Yu, Sile; He, Xingru; Pazo, Emmanuel Eric; Xu, Ling (Frontiers in Medicine, 2024)
Background: Daily use of low concentrations of atropine is recommended for children undergoing myopia control therapy. While the benefits of controlling myopia progression have been confirmed, the potential unwanted side effects on the ocular surface, pupil size, and quality of vision following administering 0.01% atropine have not been investigated. Objective: Single arm, self-control study aimed to investigate the short-term effects of 0.01% atropine topical eye drop (He Eye Hospital Co., Ltd, Shenyang, China) on pupil size and subjective quality of vision in participants with myopia. The 3 ml eyedrop contains atropine (0.01%), sodium chloride (0.9%), and benzalkonium chloride (0.005%) in aqueous solution. Methods: Thirty-three adults (66 eyes) were recruited for the study. The mean age of the participants recruited for this study was 24.91±3.36 years and registered in Clinical Trials. gov (NCT06071260). Assessments were performed at baseline and 10 hours, 14 hours, and 18 hours following the administration of 0.01% topical atropine drop (TAD). Mesopic pupil diameter (MPD), photopic pupil diameter (PPD), higher order aberration (HOA), non-invasive tear breakup time (NITBUT), tear meniscus height (TMH), tear film lipid layer (TFLL), and conjunctival hyperemia (RS). Subjective assessments included the Quality of Vision (QoV) and the Ocular Surface Disease Index Questionnaire (OSDI) questionnaires. Results: Following the use of 0.01% atropine, PPD significantly increased at all the time points (P<0.001); MPD increased significantly at 10 hours and 14 hours (P<0.001, P<0.05, respectively). A decrease in TMH and an increase in OSDI questionnaire were found until 10 and 14 hours after using atropine (P<0.001). Glare (P=0.004, P=0.003 respectively), blurred vision (P<0.0001, P=0.035), and focusing difficulties (P<0.0001, P<0.0001 respectively) were significantly higher at 10 hours and 14 hours. No significant changes were observed in HOA, NITBUT, and RS Score (all P>0.05) at all time points. Conclusion: Decreased tear meniscus height, dry eye symptoms, and visual symptoms will likely persist overnight but often diminishes within 18 hours after using 0.01% atropine eye drops.